(3GMJQGe GdbGfhf GdOhdj dMbhb GdEfSGf aj Xd GdGMJdGd GdMQHj (B: s (3eY ETGQI NGUI ddChVGY aj GdCbGdje GdadSWjfjI h GdYQGb h CaZGfSJGf (B/ s - (3EYJUGe GdYHO UGdM SGde GdhgjHjs; (3CMeO CHhGdhaG eMeO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3CcOJ GdOQGSI Gf GdGMJdGd GdMQHj ZjQ eTQhY h dG jchf fGbdB ddSjGOI Cj Cfg dG jJQJH Ydjg GfJbGd SjGOI GdEbdje GdeMJd Edi GdOhdI GdbGFeI HGdGMJdGd (B. (3ceG dG jLhR bGfhfB ddOhdI GdbGFeI HGdGMJdGd Cf JYdf VegG ddEbdje Ydi CKQ GMJdGdgG dg (B: (3h dG jJQJH Ydi gPG GdEYdGf aj MGdI UOhQg Cj CKQ bGfhfj (B. (3h jchf ddeOfjjf GdeMJdI CQGVjge GdMb aj GdebGheI GdeSdMI dbhGJ GdGMJdGd (B: (3h dG jJYGQV gPG GdMb eY bhGYO GdbGfhf GdOhdj (B: (3Hd CffG fLO JCUjdB dgPG GdMb aj GdbGfhf GdOhdj h Gdabg GdOhdj (B: (3h cPG eG LQi Ydjg GdYed GdOhdjs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi(BK 2013s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B532-587s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GMJQGe Mbhb GdEfSGfs; (3GdChVGY aj adSWjf h GdYQGb h CaZGfSJGfs; (3MGdI GdGMJdGd GdMQHjs; (3GdEOGQI GdaYdjI ddEbdje GdeMJds; (3GdMb aj GdMjGIs; (3MXQ GdJYPjH hGdeYGedI GddGfSGfjIs; (3GdMb aj GdJfbd hGdEbGeIs; (3GdeSFhdjI GdOhdjIs; (3YOe eTQhYjI GdGMJdGd GdESQGFjdjs; (3GdGHYGO GdbSQj ddeOfjjfs; (3LQGFe GdbJd VO GdeOfjjfs; (3LQGFe GdGZJUGHs; (3GdJgLjQ GdbSQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs